2019
DOI: 10.21203/rs.2.12117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orthopaedic Surgeons Perceptions of Frailty and Frailty Screening

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Hence, while frailty screening was carried out in primary settings to avert the frail status of patients, this may not be practical or applicable in the acute settings. Another study with surgeons showed that frailty screening could lead to less adverse outcomes in the peri-operative period [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, while frailty screening was carried out in primary settings to avert the frail status of patients, this may not be practical or applicable in the acute settings. Another study with surgeons showed that frailty screening could lead to less adverse outcomes in the peri-operative period [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients have a decreased physiologic reserve and may have a more significant inflammatory response to trauma, even with relatively small injuries. 28,29 CCI and ASA classification are both used to stratify patient risk prior to surgery. Our study showed that increased CCI is associated with an in increased risk for discharge to a facility and ASA class IV or V also increased the risk of post-operative complications.…”
Section: Discussionmentioning
confidence: 99%
“…40 Most surgeons understand that geriatric syndromes such as frailty impact postoperative outcomes but report that they are unsure about the value of routine screening, are reluctant to record frailty in a patient's medical record and acknowledge that its management is outside their scope of practice. 41 In addition to frailty, cognitive impairment also poses challenges for surgeons. Under-recognition of cognitive impairment could have implications for validity of informed consent and might limit a person's capacity to understand treatment options 42 and participate in shared decision-making.…”
Section: Evidence For Collaborative Perioperative Care Of Older Peoplementioning
confidence: 99%
“…The complexity of patients presenting for surgery now exceeds the capacity of any one craft group to manage independently and patients benefit from a team‐based approach to care 40 . Most surgeons understand that geriatric syndromes such as frailty impact postoperative outcomes but report that they are unsure about the value of routine screening, are reluctant to record frailty in a patient's medical record and acknowledge that its management is outside their scope of practice 41 . In addition to frailty, cognitive impairment also poses challenges for surgeons.…”
Section: The Benefits For Surgeons From Collaborative Care Of Older Pmentioning
confidence: 99%